Valganciclovir versus valacyclovir prophylaxis for prevention of cytomegalovirus: an economic perspective - Kacer, M; Kielberger, L; Bouda, Mirko; Reischig, T (Transplant infectious disease, 2015)
INTRODUCTION: Valganciclovir (vGCV) and valacyclovir (vACV) are used in cytomegalovirus (CMV) prophylaxis in renal transplant recipients. The aim of this study was to compare the economic impact of both regimens during 1-year follow-up. METHODS: A total of 117 renal transplant recipients at risk for CMV were randomized to 3-month prophylaxis either with vGCV (900 mg/day, n = 60) or vACV (8 g/day, n = 57) and their data used in a pharmacoeconomic analysis. The pharmacoeconomic evaluation involved all direct CMV-related expenses in the first year after transplantation. Sensitivity analysis was employed to examine the effects of various prices of antiviral drugs and diagnostic procedures on overall CMV-related costs. Simulation of the more expensive US healthcare perspective was performed, and a scenario involving costs of acute rejection (AR) was examined. RESULTS: Overall CMV-related costs were significantly lower in the vACV arm; median United States dollars (USD) 3473 (3108-3745) vs. USD 5810 (4409-6757; P < 0.001) per patient, respectively. Our data showed that the critical determinant of the major disparity between the prophylactic regimens was the prophylaxis price. Median cost of prophylaxis in the vACV group was USD 1729 (1527-2173) compared to USD 3968 (2683-4857) in the vGCV group (P < 0.001). In sensitivity analysis of the overall CMV-related costs, the least and the most expensive pharmacotherapy and diagnostic scenarios were used; nevertheless, the vACV arm remained markedly less expensive. Simulation considering the higher physician/nurse and hospitalization fees of the US healthcare system and the scenario including expenditure associated with AR episodes also favored vACV. CONCLUSION: VACV prophylaxis for CMV is associated with a significant 44% lower cost than vGCV at the first year after renal transplantation.
Keywords: Ganciclovir; Antiviral Agents; Kidney Transplantation; acyklovir; lidé středního věku; Acyclovir; cytomegalovirové infekce; Cytomegalovirus; Postoperative Complications; lidé; Adult; Middle Aged; dospělí; Cytomegalovirus Infections; následné studie; Female; Male; ženské pohlaví; Humans; antivirové látky; mužské pohlaví; transplantace ledvin; ganciklovir; Follow-Up Studies; valin; pooperační komplikace; Valine